Rice leaf endophytic Microbacterium testaceum: Antifungal actinobacterium confers immunocompetence against rice blast disease - Patel, Asharani; Sahu, Kuleshwar Prasad; Mehta, Sahil; Balamurugan, Alexander; Kumar, Mukesh; Sheoran, Neelam; Kumar, Shanu; Krishnappa, Charishma; Ashajyothi, Mushineni; Kundu, Aditi; Goyal, Tushar; Narayanasamy, Prabhakaran; et al. (Frontiers in Microbiology, 2022)
Genetic and functional characteristics of rice leaf endophytic actinobacterial member, Microbacterium are described. Morphotyping, multilocus sequence analysis and transmission electron microscopy indicated the species identity of the endophytic bacterium, OsEnb-ALM-D18, as Microbacterium testaceum. The endophytic Microbacterium showed probiotic solubilization of plant nutrients/minerals, produced hydrolytic enzyme/phytohormones, and showed endophytism in rice seedlings. Further, the endophytic colonization by M. testaceum OsEnb-ALM-D18 was confirmed using reporter gene coding for green fluorescence protein. MicrobacteriumOsEnb-ALM- D18 showed volatilome-mediated antibiosis (95.5% mycelial inhibition) on Magnaporthe oryzae. Chemical profiling of M. testaceum OsEnb-ALM-D18 volatilomerevealed the abundance of 9-Octadecenoic acid, Hexadecanoic acid, 4-Methyl-2-pentanol, and 2,5-Dihydro-thiophene. Upon endobacterization of rice seedlings, M. testaceumaltered shoot and root phenotype suggestive of activated defense. Over 80.0% blast disease severity reduction was observed on the susceptible rice cultivar Pusa Basmati 1 upon foliar spray with M. testaceum.qPCR-based gene expression analysis showed induction of OsCERK1, OsPAD4, OsNPR1.3, and OsFMO1 suggestive of endophytic immunocompetence against blast disease. Moreover, M. testaceumOsEnb-ALM- D18conferred immunocompetence, and antifungal antibiosis can be the future integrated blast management strategy.